A case of blunt abdominal trauma and posttraumatic acute appendicitis. - Karavokyros, Ioannis; Pikoulis, Emmanouil; Karamanakos, Panagiotis (Ulus Travma Acil Cerrahi Derg, 2004)
Acute appendicitis and blunt abdominal trauma are common surgical emergencies. Whether there is a causative relationship between these two entities has long been a subject of debate. A twenty-one-year-old male Japanese tourist presented with vague abdominal pain and dysuria that began after he had been beaten and robbed. No signs of trauma were detected on physical examination; however, there were diffuse abdominal sensitivity with maximal tenderness in the hypogastrium and rebound tenderness in the right lower quadrant. Upon no improvement with medications within 24 hours, laparotomy was performed, which revealed an inflamed appendix, a few enlarged mesenteric lymph nodes, and free peritoneal fluid that was found to be sterile. Following appendectomy, the diagnosis was confirmed by pathologic examination and the enlargement of the lymph node was attributed to non-specific reactive hyperplasia. The patient had an uneventful postoperative course, with relief of pain and fever.
Keywords: Abdominal Injuries; Abdominal Pain; Acute Disease; Adult; Appendectomy; Appendicitis; Diagnosis, Differential; Humans; Male; Wounds and Injuries